In 27 days - Gervais, Alison (Grand Rapids, Michigan : Blink, 2017)
Hadley Jamison is shocked when she hears that her classmate, Archer Morales, has committed suicide. She didn't know the quiet, reserved guy that well, but that doesn't stop her from feeling there was something she could have done to help him. Hoping to find some sense of closure, Hadley attends Archer's funeral. There, Hadley is approached by a man who calls himself Death and offers her a deal. If Hadley accepts, she will be sent back twenty-seven days in time to prevent Archer from killing himself. But when Hadley agrees to Death's terms and goes back to right the past, she quickly learns her mission is harder than she ever could have known. Hadley soon discovers Archer's reasons for being alone, and Archer realizes that having someone to confide in isn't as bad as he'd always thought. But when a series of dangerous accidents starts pushing them apart, Hadley must decide whether she is ready to risk everying - including her life - to keep Archer alive.
When Hadley Jamison hears that classmate Archer Morales has committed suicide, she feels there was something she could have done to help him. At his funeral she is approached by a man who calls himself Death and offers her a deal. If Hadley accepts, she will be sent back twenty-seven days in time to prevent Archer from killing himself. But when Hadley agrees and goes back to right the past, her mission is harder than she ever could have known. When a series of dangerous accidents starts pushing them apart, Hadley must decide whether she is ready to risk everything-- including her life-- to keep Archer alive.
Includes interview with the author and discussion questions (pages 345-348).
A Junior Library Guild selection (JLG.)
Keywords: Teenagers -- Fiction; Friendship -- Fiction; Mephistopheles -- (Legendary character) -- Fiction; Spirits -- Fiction; Suicide -- Fiction; New York (N.Y.) -- Fiction; Death (Personification) -- Fiction; Teenagers -- Suicidal behavior -- Fiction; Time travel -- Fiction; Fantasy Fiction